EKONOMIKA TÁLIM BAǴDARÍNÍŃ TALABALARÍ UShÍN RÁSMIY KOMMUNIKACIYANÍŃ ÁHMIYETI - Esanova, A.Z. (ILIM hám JÁMIYET, 2025)
This article tells future economists about the importance of formal communication, its practical benefits and skills, and ways to develop formal communication.